Passive smoking as a risk factor among older adults: an ordered probability approach for Türkiye - Ünver, Şeyda; Tekmanli, Hasan Hüseyin; Alkan, Ömer (Frontiers in Public Health, 2023)
Background/aim Older adults represent a significant proportion of the population of many societies, and being one of the disadvantaged groups, they struggle with various difficulties in their social lives. Undoubtedly, passive smoking is one of these difficulties. Passive smoking among older adults, which is an important public health problem, is an issue that needs to be investigated. The aim of this study is to determine the relationship between the demographic and socio-economic characteristics of adults aged 60 and older in Türkiye and their exposure to secondhand smoke (SHS). Methods In this study, a microdata set of the 2016 and 2019 Turkey Health Survey conducted by the Turkish Statistical Institute (TUIK) was used. This survey was conducted by TUIK in the relevant years using a stratified sampling method to best represent the whole of Turkey. The study considered only demographic and socio-economic characteristics to investigate passive smoking. Since all the variables used in the study were categorical, the relationship between the dependent variable and the independent variables was first investigated using chi-square tests. In addition, since the dependent variable has an ordered-categorical probability form, the generalized ordinal logit model was used for the analysis of passive smoking and related factors. Results The rate of exposure to tobacco smoke of older adults who participated in the study in 2016 was 16%, while the rate of those who participated in the study in 2019 was 21%. Conclusion According to the findings of the study, older, uneducated, and uninsured smokers carry a more serious SHS risk. It may be beneficial for society for policy makers to carry out studies by considering these features a priority and focusing on policies in this context. Expanding smoke-free areas to cover older adult, increasing penalties as a deterrent, facilitating education, increasing state support for education, increasing education and public service announcements about tobacco harms, and facilitating social security are the main examples. This study’s findings are crucial as a source of information for the development of policies and programs aimed at preventing the exposure of older adults to tobacco smoke.